Răspuns :
a+b=490
a-b=28 ⇒ a=b+28
=====================
b+28+b=490
2*b+28=490
2*b=490-28
2*b=462
b=462:2
b=231
a=231+28
a=259
a-b=28 ⇒ a=b+28
=====================
b+28+b=490
2*b+28=490
2*b=490-28
2*b=462
b=462:2
b=231
a=231+28
a=259
a-b=28
a+b=490→a=490-b
490-b-b=28
490-2b=28
490-28=2b
462=2b
b=462:2
b=231
Acum îl înlocuim pe "b" în oricare din cele două ecuații:
a+231=490
a=490-231
a=259
=>a=259
b=231
Facem proba:
259-231=28
259+231=490
a+b=490→a=490-b
490-b-b=28
490-2b=28
490-28=2b
462=2b
b=462:2
b=231
Acum îl înlocuim pe "b" în oricare din cele două ecuații:
a+231=490
a=490-231
a=259
=>a=259
b=231
Facem proba:
259-231=28
259+231=490